2018
DOI: 10.1177/1045389x18770905
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating actuator distributions in simply supported truncated thin conical shell with embedded piezoelectric layers

Abstract: In this investigation, distributed modal actuator forces of simply supported truncated conical shell embedded by a piezoelectric layer are studied. Piezoelectric layer is distributed on the conical shell surface as actuators. Three types of distributions are considered: longitudinal, circumferential, and diagonal distributions. First, electromechanical equations of the conical shell with embedded piezoelectric actuator layer are extracted. Then modal expansion method is used to define independent modal charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The layout of piezoelectric actuators can be designed based on the following centralized criteria: controllable/observable method, system energy criterion, the system response criterion, control/observation overflow criterion, and piezoelectric execution designed based on different layout criteria has different advantages. [ 56 ] For example, Xu et al explored the influence of different piezoelectric arrangements on the piezoelectric constant and mechanical quality of the composite beam, [ 57 ] as shown in Figure . Through exploring the distribution of piezoelectric sheets on different positions on the board, they found that the different distributed caused a large difference in piezoelectric voltage constant, mechanical property quality factor, and acoustic impedance value.…”
Section: Piezoelectric Actuatorsmentioning
confidence: 99%
“…The layout of piezoelectric actuators can be designed based on the following centralized criteria: controllable/observable method, system energy criterion, the system response criterion, control/observation overflow criterion, and piezoelectric execution designed based on different layout criteria has different advantages. [ 56 ] For example, Xu et al explored the influence of different piezoelectric arrangements on the piezoelectric constant and mechanical quality of the composite beam, [ 57 ] as shown in Figure . Through exploring the distribution of piezoelectric sheets on different positions on the board, they found that the different distributed caused a large difference in piezoelectric voltage constant, mechanical property quality factor, and acoustic impedance value.…”
Section: Piezoelectric Actuatorsmentioning
confidence: 99%
“…These various controllers can be applied to any structure to reduce undesired vibration. For example, for vibration reduction of conical shells there are many related articles in which piezoelectric patches with different distributions used [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…From the mechanical point of view, most of the articles in this regard [ 1 , 4 , 8 , 9 ] are based on the study of the free vibration of conical shells, to act on the natural oscillation modes under different displacement constraints. However, it should be noted that Li et al [ 10 ] analytically studied the forced vibrations of conical shells, obtaining the equations of motion under different external dynamic loads.…”
Section: Introductionmentioning
confidence: 99%